2015
DOI: 10.1186/s40104-015-0035-y
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol levels in skimmed milk during the first 22 weeks of lactation and response to short-term metabolic stress and lameness in dairy cows

Abstract: BackgroundCortisol is secreted into blood in reaction to acute stress, but also in phases of diminished feed intake and changed animal behavior. As cows do not always show clear signs of discomfort, reliable diagnostic markers could be used to provide information regarding individual cows’ distress. The objective of this study was to establish an ether free immunoassay for the detection of cortisol and to determine values during the first 22 weeks of lactation. Furthermore, the response in milk cortisol levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…and subsequent decrease appears to be typical of healthy postpartum cows, and agrees with the results from other biological samples such as milk (Fukasawa et al, 2008;Gellrich et al, 2015). In this study, such a typical pattern was observed in the normal cows with a peak cortisol concentration at L1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…and subsequent decrease appears to be typical of healthy postpartum cows, and agrees with the results from other biological samples such as milk (Fukasawa et al, 2008;Gellrich et al, 2015). In this study, such a typical pattern was observed in the normal cows with a peak cortisol concentration at L1.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that hair cortisol concentrations were significantly associated with hock health status. Hock scores are often correlated with lameness (Kester, Holzhauer, & Frankena, ), and lame cows were reported to have higher cortisol concentrations in hair (Comin et al, ) and milk (Gellrich, Sigl, Meyer, & Wiedemann, ). To our knowledge, this is the first report showing that hock health assessed by a visual scoring method is associated with hair cortisol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…High circulating cortisol concentrations were reported to be linked with reduced milk TG -treatment group (animals injected with carprofen); CG -control group (animals injected with 0.9% NaCl); *P < 0.005 yields. Gellrich et al (2015) found that correlation analyses indicated a significant negative association of milk cortisol and milk yield and milk yield-dependent variables (i.e. protein yield and fat yield).…”
Section: Discussionmentioning
confidence: 95%
“…In response to pain, the physiological activity of the hypothalamus-pituitary-adrenal axis and the autonomous nervous system is activated resulting in the release of cortisol; the main glucocorticoid hormone [64]. Accordingly, a significant increase in the plasma concentration of cortisol was reported in clinically lame cows compared to non-lame groups [65,66]. Similar results were observed in lame cows compared to the untreated group after inducing lameness using oligofructose approach [54] and evaluation of cortisol level in the milk of lame cows [66].…”
Section: Physiological Parameters and Biomarkersmentioning
confidence: 99%